A Marketing Plan for Applying 5W1H (What, Why, Where, When, Who, and How) in Design Postgraduate Degrees: A Case Study from Thailand - Kasemsarn, Kittichai (My University, 2022)
Postgraduate degrees in design have changed due to the latest technology and trends. Moreover, there is a lack of research regarding the relationship between the behavior of students and marketing plans for the curriculum. Therefore, this research aims to explore the concept of treating postgraduate design students in Thailand as customers by applying 5W1H (what, why, where, when, who, and how) to the criteria, behaviors, and trends in choosing the curriculum. This study set up online in-depth interviews for twenty postgraduate degree students in this area from four public universities in Thailand in April 2020. Raw data were transcribed into a thematic coding analysis. The findings illustrate that design students need new and updated knowledge (what), and choose the course due to its reputation (why) by themselves without recommendations from others (who). Additionally, they are aware of social media advertising (where), and search in-depth information before the end of the year or six months before term begins (when) from official websites to compare curriculums (how). Finally, this research contributes to knowledge about how marketing plans (5W1H) can understand how postgraduate design students choose their curriculums. As a result, universities could adapt, design, and offer appropriate curriculums and promote them effectively to students.
Keywords: 5W1H; Design; Marketing; Postgraduate degrees; Thailand